Spirituality and Subjective Well-Being: The Moderating Role of Religious Moderation in Klepu Village, Ponorogo - Nugraheni, Adelia; Rusdiana, Fendi Krisna (Universitas Islam Negeri Raden Intan Lampung, 2026)
Psychological well-being is the basic quality of life of an individual that is theoretically correlated with the spiritual dimension and religious orientation. This study aims to examine the influence of spirituality on subjective well-being by positioning religious moderation as a moderator variable in the context of a pluralistic society. Using a quantitative correlational design, data were collected from 39 respondents from Klepu Village, Ponorogo, through a purposive sampling technique. The research instruments included the subjective well-being scale, spirituality, and religious moderation, which were analyzed using Moderated Regression Analysis (MRA) with a bootstrapping technique to ensure statistical robustness. The results of the analysis indicate that spirituality has a positive effect on subjective well-being. However, religious moderation was not proven to significantly moderate the relationship. These empirical findings are discussed comprehensively by integrating the historical-sociological context of the plurality of Klepu Village, which states that moderate attitudes have become a cultural norm. This study offers practical implications for Islamic guidance and counseling services, particularly in the development of intervention modules that are sensitive to the local religious context.